A study of light-induced stomatal response in Arabidopsis using thermal imaging - Orzechowska, Aleksandra; Trtílek, Martin; Tokarz, Krzysztof; Rozpądek, Piotr (Biochemical and biophysical research communications, 2020)
Thermal imaging was used to study the early stage response to light-induced heating of Arabidopsis thaliana leaves. Time-series thermograms provided a spatial and temporal characterization of temperature changes in Arabidopsis wild type and the ost1-2 mutant rosettes exposed to excessive illumination. The initial response to high light, defined by the exponential increase in leaf temperature of ost1-2 gave an increased thermal time constant compared to wild type plants. The inability to regulate stomata in ost1-2 resulted in enhanced stomatal conductance and transpiration rate. Under strong irradiation, a significant decline in the efficiency of photosystem II was observed. This study evaluates infrared thermography kinetics and determines thermal time constants in particular, as an early and rapid method for diagnosing the prime indicators of light stress in plants under excessive light conditions.
Keywords: Plant Leaves; Photosystem II Protein Complex; proteiny huseníčku; Photosystem II efficiency; Temperature; termografie; Thermography; teplota; mutace; Arabidopsis Proteins; Infrared thermal imaging; listy rostlin; Plant Stomata; Protein Kinases; Arabidopsis; fotosystém II (proteinový komplex); Light-induced temperature kinetics; Stomatal conductance; proteinkinasy; průduchy rostlin; Mutation